2023
DOI: 10.1002/anie.202306427
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Guest‐Host‐Receptor Recognitions Precisely Guide Ciprofloxacin to Eliminate Intracellular Staphylococcus aureus

Abstract: Staphylococcus aureus (S. aureus) is able to hide within host cells to escape immune clearance and antibiotic action, causing life‐threatening infections. To boost the therapeutic efficacy of antibiotics, new intracellular delivery approaches are urgently needed. Herein, by rational design of an adamantane (Ada)‐containing antibiotic‐peptide precursor Ada‐Gly‐Tyr‐Val‐Ala‐Asp‐Cys(StBu)‐Lys(Ciprofloxacin)‐CBT (Cip‐CBT‐Ada), we propose a strategy of tandem guest‐host‐receptor recognitions to precisely guide cipro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…A recent study showed that further aggregation of AIEgens (we call it “dual-AIE” in this work) significantly improves imaging sensitivity due to their enhanced AIE fluorescence brightness . 3 years before this work was carried out, we also reported a “dual-AIE” probe based on a biocompatible click reaction between 2-cyanobenzothiazole (CBT) and d -cysteine (Cys), the fluorescence of which was lightened and enhanced through simultaneous intra- and intermolecular aggregations for highly sensitivity imaging of furin activity in vitro and in cells . Naturally, we think that an NIR “dual-AIE” fluorogen should be able to sensitively monitor (or image) AD occurrence and progression, which, to the best of our knowledge, has not been reported.…”
Section: Introductionmentioning
confidence: 92%
“…A recent study showed that further aggregation of AIEgens (we call it “dual-AIE” in this work) significantly improves imaging sensitivity due to their enhanced AIE fluorescence brightness . 3 years before this work was carried out, we also reported a “dual-AIE” probe based on a biocompatible click reaction between 2-cyanobenzothiazole (CBT) and d -cysteine (Cys), the fluorescence of which was lightened and enhanced through simultaneous intra- and intermolecular aggregations for highly sensitivity imaging of furin activity in vitro and in cells . Naturally, we think that an NIR “dual-AIE” fluorogen should be able to sensitively monitor (or image) AD occurrence and progression, which, to the best of our knowledge, has not been reported.…”
Section: Introductionmentioning
confidence: 92%
“…FLI as one of the most common bioimaging approaches mainly depends on fluorescent dyes capable of absorbing external excitation light energy and further emitting FL signals in the excited state . FLI technique has gained widespread applications in disease diagnosis because of its exceptional spatiotemporal resolution and noninvasive characteristic. , With the rapid advancement of technology, conventional “always-on” FL probes with weak specificity and contrast have been replaced by smart “off-on” FL probes. These intelligent counterparts show the FL “off” state and, once entering the disease location, they can be cleaved by corresponding enzymes and turn into the FL “on” state .…”
Section: Bioimaging Applications Of Enzyme-instructed Cbt-cys-like Cl...mentioning
confidence: 99%
“…To address these challenges, researchers have recently developed innovative solutions such as antibody-modified antibiotics, antibiotic-peptide conjugates, bacterial metabolic labeling, etc . For instance, the conjugation of an anti- S. aureus antibody to an antibiotic known as rifalogue can markedly enhance the antibacterial potency of the antibiotic to kill intracellular bacteria . Nonetheless, variations in antibody properties might compromise the effectiveness, potentially limiting their broader utilization.…”
Section: Introductionmentioning
confidence: 99%